HNF1A variant, energy-reduced diets and insulin resistance improvement during weight loss: The POUNDS Lost trial and DIRECT - Huang, T.; T. Wang; Heianza, Y.; Sun, D.; Ivey, K.; Durst, R.; Schwarzfuchs, D.; Stampfer, M. J.; Bray, G. A.; Sacks, F. M.; Shai, I.; Qi, L. (Diabetes Obes MetabDiabetes Obes MetabDiabetes Obes Metab, 2018)
AIM: To determine whether weight-loss diets varying in macronutrients modulate the genetic effect of hepatocyte nuclear factor 1alpha (HNF1A) rs7957197 on weight loss and improvement of insulin resistance. MATERIALS AND METHODS: We analysed the interaction between HNF1A rs7957197 and weight-loss diets with regard to weight loss and insulin resistance improvement among 722 overweight/obese adults from a 2-year randomized weight-loss trial, the POUNDS Lost trial. The findings were replicated in another independent 2-year weight-loss trial, the Dietary Intervention Randomized Controlled Trial (DIRECT), in 280 overweight/obese adults. RESULTS: In the POUNDS Lost trial, we found that a high-fat diet significantly modified the genetic effect of HNF1A on weight loss and reduction in waist circumference (P for interaction = .006 and .005, respectively). Borderline significant interactions for fasting insulin and insulin resistance (P for interaction = .07 and .06, respectively) were observed. We replicated the results in DIRECT. Pooled results showed similar significant interactions with weight loss, waist circumference reduction, and improvement in fasting insulin and insulin resistance (P values for interaction = .001, .005, .02 and .03, respectively). Greater decreases in weight, waist circumference, fasting insulin level and insulin resistance were observed in participants with the T allele compared to those without the T allele in the high-fat diet group (P = .04, .03 and .01, respectively). CONCLUSIONS: Our replicable findings provide strong evidence that individuals with the HNF1A rs7957197 T allele might obtain more benefits in weight loss and improvement of insulin resistance by choosing a hypocaloric and high-fat diet.